Geographic variation in the advertisement call of Trachycephalus typhonius Anura: Hylidae) based on South American samples - Zaracho, Víctor Hugo; Aguiar, Leonardo Dionel; Giaretta, Ariovaldo Antonio (Zootaxa, 2018)
Previously described calls of Trachycephalus typhonius (Linnaeus, 1758) correspond to several populations from Central and South America, but in general, these descriptions were brief and often based on a single recorded individual. Here, based on an expressive sample, we re-describe the advertisement calls of T. typhonius using recordings from populations in Brazil and Argentina. Additionally, we discuss geographical variation of calls, comment on their frequency band structure and compare calls with those described for other species of Trachycephalus. Calls of 32 males were recorded and temporal and spectral features of 269 calls were measured. To search for discrimination among three populations sampled we used the Random Forest (RF) model, Multidimensional Scaling Analysis (MDS) and Wilcoxon-Mann-Whitney Rank Sum Test. The advertisement calls of T. typhonius consist of a multipulsed note of 343–540 ms of duration, emitted at regular intervals, with up to three emphasized frequency bands. Dominant frequency ranged between 1705–2750 Hz. Calls from Rondônia (Brazil) were significantly different from those recorded in Argentina and Minas Gerais (Brazil) in relation to pulse rate and dominant frequency. Populations from Minas Gerais and Argentina differed in dominant frequency of calls. Such population differences can be partly attributed to differences in prevalence of calling sites (immersed in water vs. perches on vegetation), but can also hint at the existence of cryptic species diversity under this taxon.